PROSES PEMBUATAN ETHANOL SEMIKONTINYU MELALUI REKAYASA ALAT FERMENTOR FLUIDISASI - Fathorrahman Fathorrahman; A. Swastika S; N. Yuliana; S.P. Abrina A (Universitas Tribhuwana Tunggadewi, 2012)
Bioetanol is alternative fuel substitute potentially and ethanol is a process of biomass fermentation by using microorganisms. This research is a solution of obstacles faced in fermentation process of batch, which is more commonly used ethanol that is the existance of production of ethanol which will poison microorganisms in fermentation process and even stop the growth and production of ethanol. The research result is expected to give possibility to produce technological innovation by knowing maximum results of the opening of flow rate to the ethanol productivity and efficiency process and quality of product. This technology possibly applied as effective and efficient technology for ethanol production system. The method of this research uses system of semi continue using fluidisasi fermentation using saccharomyces cerevisiae amobilzed which can improve effectiveness the process of manufacture ethanol less than 50 hours faster than conventional fermentation (in batch) commonly the results obtained only maximally 13,85 for 72 hours (3 days). The results showed that the process of semi continue fluidisasi fermentation is amobilized it done only for 24 hours and obtained 20% ethanol level of 300 opening rate of fluid flow, 22% ethanol level of 600 opening rate of fluid flow, and 23% ethanol level of 900 opening rate of fluid flow